Review of Male Breast Disorder in Medical City - Al-Obaidi, Safa M.; Hussein, Humam A.; Awazli, Lutfi G.; Tajer, Salah M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Although uncommon, diseases of the male breast engender a tremendous emotional response. Fortunately, most diseases present with a mass and are easily detected. Unlike the female breast, only ducts but no lobules are present.Objectives: The aim of this descriptive study is to present the clinical, pathological and ultrasonographic features of different breast lesions amongst males.Patients & methods: Data obtained from 93 male patients with breast disorders collected between the first of January 2008 to the end of December 2009 and based on clinical examination were done in surgical wards in Baghdad teaching hospital and the main referral training centre for early detection of breast tumors.Results: Gynecomastia was the most common pathological abnormality of the male breast (77 patients, 82.8%). Most of the patients presented in the 2nd decade of life. Amongst the malignant conditions, infiltrating ductal carcinoma was the only malignant tumor detected (5 patients, 5.37%).Conclusion: The majority (94.63%) of male breast lesions are benign. Ultrasonographic examination is useful-but not the only for distinguishing benign versus malignant lesions, FNAC and histopathological examination yield the final diagnosis.